Biomodulatory effect of low intensity laser (830 nm.) in neural model 9L/lacZ (Research, Society and Development, 2021)
Currently, research is advancing with low-intensity laser (LIL) in cells of the central nervous system, with the aim of  evaluating the benefits of this therapy in neurological disorders such as Alzheimer's, stroke, ischemia, epilepsy, among others. The aim of this study was to verify the biomodulatory and biostimulatory effects of LIL in neural cell culture. Diode laser at wavelength λ = 830 nm, power 40 mW, in continuous mode, was applied on the 9L/lacZ cell line with energy densities of 0.5 to 3 J/cm2. The analysis was performed 24 hours after irradiation, the results of cell viability showed a difference between the control and irradiated groups. As for the occurrence of apoptosis, no significant manifestation was observed between the control group compared to the irradiated group (P = 0.9956); therewas a significant difference between apoptosis and death by necrosis between the control and treated groups (P